PENGARUH DISIPLIN BELAJAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN SOSIOLOGI KELAS XI IPS - Hendra Hendra; Gusti Budjang; Rustiyarso Rustiyarso (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2017)
AbstractThe title of this research was “The effect of learning discipline towards the studentslearningoutcomes in sociology subject at XI IPS of SMA Santun Untan Pontianak. The purposeof this research was to investigate whether or not the effect of learning discipline towards thestudents learning outcomes. The problems formulation of this research are: 1. How the eleventhgrade students learning discipline in sociology subject. 2. How the students learning outcomes insociology subject at the eleventh grade. 3. What is the effect of learning discipline towards thestudents learning outcomes in sociology subject at the eleventh grade. The research appliedquantitative method by using the effect of inferential statistic. The data was collected by usingdirect communication and indirect communication and documentary study. The data wascollected by using questionnaire and notes which was collected from the 30 students. Thehypothesis result of this research was there was the positive effect and significance between learning discipline towards learning outcomes with r calculated 3.890> the t table 2,048. While,the value of equation regression was Y= 10.670 + 0.544X, showed that the learning discipline (Xvariable) increased 1, then the learning outcomes (Y variable) increased 0.544. the determinantscore adjust R2 = 0,406 which was means there was the effect of learning discipline towardslearning outcomes as big as  40.6 % which was classified as average and 59.4% determined byanother factor which was don’t discussed in this research. Key words: Learning Discipline, Learning Outcomes